Fabrication and characterization of mullite-whisker-reinforced lightweight porous materials with AlF3·3H2O. Issue 10 (15th May 2022) - Deng, Xiangong; Ji, Peng; Yin, Jiaqiang; Wang, Yunlong; Song, Chenghao; Li, Saisai; Zhang, Yi; Ding, Xiang; Ran, Songlin; Zhang, Haijun; Deng, Hailiang
Abstract: Mullite-whisker-reinforced lightweight porous materials were fabricated by the particle stabilization method using fly ash and calcined bauxite as raw materials, and AlF3 ·3H2 O as an additive. The effect of AlF3 ·3H2 O on the phase composition, volume density, porosity, microstructure, mechanical performance, and heat conductivity of mullite-whisker-reinforced lightweight porous materials was explored. With an increase in the AlF3 ·3H2 O content, the linear shrinkage, volume density, compressive strength, flexural strength, and heat conductivity of lightweight porous materials increased and their porosity decreased. When the AlF3 ·3H2 O content was 9 wt%, flexural and compressive strengths of lightweight porous material samples with a porosity of 72.3% and an average whisker length of ∼19.2 μm were 17.8 and 31.0 MPa, respectively, and the heat conductivity was maintained at a minimal value of 0.092 W (m K) −1 .